A bandpass filter using modified half mode substrate integrated waveguide technique. Issue 4 (28th October 2014) - Hao, Zhang‐Cheng; Huo, Xin‐Ping
ABSTRACT: This article reports a novel bandpass filter using modified half mode substrate integrated waveguide technique. The via‐fences are deployed as impedance inverters for the proposed filter to reduce its footprints, which are extracted by using a full‐wave electromagnetic simulator HFSS for the filter design. Detailed design procedure is discussed. A bandpass filter having a center frequency of 10.03 GHz and a pass band from 9.78 to 10.3 GHz is designed for demonstration, and experiments are carried out for the validation. Good agreements between experiment and simulated results are obtained, which show that the proposed filter has a compact size, a low insertion loss, and a high selectivity. It is attractive for the radio communication system. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:277–281, 2015.